Analisis Pemanfaatan Keanekaragaman Ekosistem Mangrove oleh Masyarakat Pesisir Pantai Paluh Getah - Geby Paulina; Immanuel Sinabang; Klarita Dwijayanti Waruwu; Winda Rahayu; Meilinda Suriani Harefa (Jurnal Social Science, 2023)
Mangrove ecosystems, apart from functioning ecologically, also have economic and social value. The problem is that mangrove ecosystems are threatened by careless ecosystem management. The research objectives were (1) to analyze the plants, their utilization, and the processing of mangrove plants for the life of the surrounding community. The results showed that the types of Rhizophora apiculata, Avicennia marina, Nypa, Sonneratia caseolaris, and Acanthus ilicifolius grew in the Paluh Gum area. Mangrove plants are used and processed by the community into various snacks and crafts.